Odpowiedzi

2009-11-04T19:16:42+01:00
4x³-3x-x⁴+2x³+3x = -x⁴+4x³+2x³-3x+3x = -x⁴+6x³

x⁴-2x³-3x+2(4x³-3x)-½(3x²-6x+2) = x⁴-2x³-3x+8x³-6x-1,5x²+3x-1 = x⁴+6x³-1,5x²-6x-1

(4x³-3x)×(3x²-6x+2)+x⁴-2x³-3x = 12x⁵-24x⁴+8x³-9x³+18x²-6x+x⁴-2x³-3x = 12x⁵-23x⁴-3x³+18x²-3x
2009-11-04T19:40:45+01:00
U(x)=4x³-3x
V(x)=3x²-6x+2
W(x)=x⁴-2x³-3x

1.U(x)-W(x)
4x³-3x-(x⁴-2x³-3x)=4x³-3x-x⁴+2x³+3x=-x⁴+6x³

2.W(x)+2U(x)-½V(x)
x⁴-2x³-3x+2(4x³-3x)-½(3x²-6x+2)=x⁴-2x³-3x+8x³-6x-³/₂x²+3x-1= x⁴-³/₂x²-1

U(x)×V(x)+W(x)
(4x³-3x)×(3x²-6x+2)+(x⁴-2x³-3x)=12x⁶-24x⁴+8x³-9x³+18x²-6x+x⁴-2x³-3x=12x⁶-23x⁴+x³+18x²-9x
Najlepsza Odpowiedź!
2009-11-04T22:38:23+01:00
U(x)-W(x)=4x³-3x-x⁴+2x³+3x=-x⁴+6x³
W(x)+2U(x)-1/2V(x)=x⁴-2x³-3x+2*(4x³-3x)-1/2*(3x²-6x+2)=x⁴-2x³-3x+8x³-6x-3/2x²+3x-1=x⁴+6x³-3/2x²-6x-1
U(x)*V(x)+W(x)=(4x³-3x)*(3x²-6x+2)+(x⁴-2x³-3x)=12x⁵-24x⁴+8x³-9x³+18x²-6x+x⁴-2x³-3x=12x⁵-23x⁴-3x³+18x²-9x